Answer:
the correct symbol is: Δ
Step-by-step explanation:
In a hand of 5 cards, you want 4 of them to be of the same rank, and the fifth can be any of the remaining 48 cards. So if the rank of the 4-of-a-kind is fixed, there are
possible hands. To account for any choice of rank, we choose 1 of the 13 possible ranks and multiply this count by
. So there are 624 possible hands containing a 4-of-a-kind. Hence A occurs with probability
![\dfrac{\binom{13}1\binom44\binom{48}1}{\binom{52}5}=\dfrac{624}{2,598,960}\approx0.00024](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cbinom%7B13%7D1%5Cbinom44%5Cbinom%7B48%7D1%7D%7B%5Cbinom%7B52%7D5%7D%3D%5Cdfrac%7B624%7D%7B2%2C598%2C960%7D%5Capprox0.00024)
There are 4 aces in the deck. If exactly 1 occurs in the hand, the remaining 4 cards can be any of the remaining 48 non-ace cards, contributing
possible hands. Exactly 2 aces are drawn in
hands. And so on. This gives a total of
![\displaystyle\sum_{a=1}^4\binom4a\binom{48}{5-a}=886,656](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Ba%3D1%7D%5E4%5Cbinom4a%5Cbinom%7B48%7D%7B5-a%7D%3D886%2C656)
possible hands containing at least 1 ace, and hence B occurs with probability
![\dfrac{\sum\limits_{a=1}^4\binom4a\binom{48}{5-a}}{\binom{52}5}=\dfrac{18,472}{54,145}\approx0.3412](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csum%5Climits_%7Ba%3D1%7D%5E4%5Cbinom4a%5Cbinom%7B48%7D%7B5-a%7D%7D%7B%5Cbinom%7B52%7D5%7D%3D%5Cdfrac%7B18%2C472%7D%7B54%2C145%7D%5Capprox0.3412)
The product of these probability is approximately 0.000082.
A and B are independent if the probability of both events occurring simultaneously is the same as the above probability, i.e.
. This happens if
- the hand has 4 aces and 1 non-ace, or
- the hand has a non-ace 4-of-a-kind and 1 ace
The above "sub-events" are mutually exclusive and share no overlap. There are 48 possible non-aces to choose from, so the first sub-event consists of 48 possible hands. There are 12 non-ace 4-of-a-kinds and 4 choices of ace for the fifth card, so the second sub-event has a total of 12*4 = 48 possible hands. So
consists of 96 possible hands, which occurs with probability
![\dfrac{96}{\binom{52}5}\approx0.0000369](https://tex.z-dn.net/?f=%5Cdfrac%7B96%7D%7B%5Cbinom%7B52%7D5%7D%5Capprox0.0000369)
and so the events A and B are NOT independent.
Answer:
Formula for the Arc length is given by:
![\text{Arc length} = 2 \pi r \cdot \frac{\theta}{360^{\circ}}](https://tex.z-dn.net/?f=%5Ctext%7BArc%20length%7D%20%3D%202%20%5Cpi%20r%20%5Ccdot%20%5Cfrac%7B%5Ctheta%7D%7B360%5E%7B%5Ccirc%7D%7D)
As per the statement:
radius of circle(r) = 6 units
Angle (
) =
radian
Use conversion:
![1 rad = \frac{180}{\pi}](https://tex.z-dn.net/?f=1%20rad%20%3D%20%5Cfrac%7B180%7D%7B%5Cpi%7D)
= ![\frac{180}{\pi} \cdot \frac{7 \pi}{8} = \frac{1260}{8} = 157.5^{\circ}](https://tex.z-dn.net/?f=%5Cfrac%7B180%7D%7B%5Cpi%7D%20%5Ccdot%20%5Cfrac%7B7%20%5Cpi%7D%7B8%7D%20%3D%20%5Cfrac%7B1260%7D%7B8%7D%20%3D%20157.5%5E%7B%5Ccirc%7D)
then;
substitute these given values we have;
Use value of ![\pi = 3.14](https://tex.z-dn.net/?f=%5Cpi%20%3D%203.14)
![\text{Arc length} = 2\cdot 3.14 \cdot (6) \cdot \frac{157.5^{\circ}}{360^{\circ}}](https://tex.z-dn.net/?f=%5Ctext%7BArc%20length%7D%20%3D%202%5Ccdot%203.14%20%5Ccdot%20%286%29%20%5Ccdot%20%5Cfrac%7B157.5%5E%7B%5Ccirc%7D%7D%7B360%5E%7B%5Ccirc%7D%7D)
or
![\text{Arc length} = 2\cdot 3.14 \cdot (6) \cdot 0.4375](https://tex.z-dn.net/?f=%5Ctext%7BArc%20length%7D%20%3D%202%5Ccdot%203.14%20%5Ccdot%20%286%29%20%5Ccdot%200.4375)
Simplify:
![\text{Arc length}=16.485](https://tex.z-dn.net/?f=%5Ctext%7BArc%20length%7D%3D16.485)
Therefore, the arc length of the arc substended in a circle with radius 6 units an angle of 7 pi/8 is 16.485 units
Answer:
![(7C4) (2x)^4 (-y)^{7-4}](https://tex.z-dn.net/?f=%20%287C4%29%20%282x%29%5E4%20%28-y%29%5E%7B7-4%7D)
And replacing we got:
![35 (2^4) x^4 (-y)^{-3}](https://tex.z-dn.net/?f=%2035%20%282%5E4%29%20x%5E4%20%28-y%29%5E%7B-3%7D)
And then the final term would be:
![-560 x^4 y^3](https://tex.z-dn.net/?f=%20-560%20x%5E4%20y%5E3)
Step-by-step explanation:
For this case we have the following expression:
![(2x-y)^7](https://tex.z-dn.net/?f=%20%282x-y%29%5E7)
And we can use the binomial theorem given by:
![(x+y)^n =\sum_{k=0}^n (nCk) x^k y^{n-k}](https://tex.z-dn.net/?f=%20%28x%2By%29%5En%20%3D%5Csum_%7Bk%3D0%7D%5En%20%28nCk%29%20x%5Ek%20y%5E%7Bn-k%7D)
And for this case we want to find the fourth term and using the formula we have:
![(7C4) (2x)^4 (-y)^{7-4}](https://tex.z-dn.net/?f=%20%287C4%29%20%282x%29%5E4%20%28-y%29%5E%7B7-4%7D)
And replacing we got:
![35 (2^4) x^4 (-y)^{-3}](https://tex.z-dn.net/?f=%2035%20%282%5E4%29%20x%5E4%20%28-y%29%5E%7B-3%7D)
And then the final term would be:
![-560 x^4 y^3](https://tex.z-dn.net/?f=%20-560%20x%5E4%20y%5E3)